Numerical Study of the Force Transfer Mechanism and Seismic Behavior of Masonry Infilled RC Frames with Windows Opening - Ebrahim Khalilzadeh Vahidi; Reza Moradi (Salehan Institute of Higher Education, 2019)
Masonry infilled walls are widely used in reinforced concrete (RC) frams worldwide. However, infilled RC frame building failure is a common mode in destructive earthquakes. Further researcher is needed to bring insightful understandings into the behaviors of these structures. Therefore, this study investigates seismic parameters, ultimate tensile damage, and force transfer mechanisms in a reinforced concrete structure under in-plan load. For this purpose, the definitions and the relevant literature were reviewed. Then, an analytical software supporting an infill model was selected and described altogether with a particular modeling approach. Calibrating software results with those presented by Abdulhafez et al. (2014), the researchers designed a series of planer one-story one-bay reinforced concrete frames upon ACI 318M-14 Building Code. The seismic behavior of infilled frames were also studied using finite element method. Force transfer mechanisms in infilled frame with opening, which is one of the important items, was investigated in this study. Comparing the analysis outcomes with the bar frame, it was indicated that the ultimate load, stiffness, and toughness of the full in-filled frame were increased while the ductility was decreased. It was also revealed that the presence of opening in infilled frame decreased the ultimate load, stiffness and toughness corresponding full infilled frame. In addition, the increasing of opening size increased the reduction of the ultimate load, stiffness and toughness.